Old & curious : the history of James Wilson's bookshop - Wilson, Roger Burdett (James Wilson, 1960)
In this book the author, who represents the third generation of a bookselling family, sets out to trace the history of a typical provincial secondhand and antiquarian bookshop from the apprenticeship of the young James Wilson in the sixties of the last century to the present day.